ORAL INTAKE OF LOADING DOSES OF ANTIARRHYTHMIC DRUGS FOR SINUS RHYTHM RESTORATION IN ATRIAL FIBRILLATION - E. O. Khamitsayeva; P. K. Janashya; E. Y. Bogdanova; N. M. Shevchenko (Российский кардиологический журнал)
Oral intake of loading doses of antiarrhythmic drugs for sinus rhythm restoration in atrial fibrillation.